Perubahan Perilaku Masyarakat Petani Muslim Undaan Kudus terhadap Sistem Penanggalan Jawa Pranata Mangsa 2000-2018: Changes in the Behavior of the Undaan Kudus Muslim Farming Society towards the Pranata Mangsa Javanese Calendar System 2000-2018 - Musta'id, Ahmad (Nur Science Institute, 2021)
This study discusses a socio-cultural history of Islam in a society regarding the reflection of the Javanese people's ability to read natural signs to determine the calculation of the seasons that will be used in farming, which is called Pranata Mangsa. The existence of the Pranata Mangsa Javanese calendar which later developed became a guideline in farming activities for Muslim farming communities in Undaan Kudus. However, if we look at several phenomena from the early 2000s AD to the present, especially regarding the seasons, of course there are many seasonal changes that occur on this Earth. The changing seasons on Earth occur due to various factors. This factor is due to the existence of several natural phenomena. This research uses historical methods and anthropological approaches. The anthropological approach can serve to study the socio-cultural background of past events, while history serves to study the cultural changes that occurred in the Muslim farming community of Undaan Kudus. This study shows that the socio-cultural conditions of the Muslim farming community are changing. The Muslim farming community of Undaan Kudus which was initially very thick with the guidelines of Pranata Mangsa with various religious ceremonies, gradually underwent a change by following the existence of modernism due to difficulties in reading natural signs.